Determination of Aflatoxin M1 Contamination and Integrity as well as Credibility - R Ataee; A Mehrabi Tavana; MH Ataee (Tehran University of Medical Sciences, 2012)
Aspergillums can produce and secrete directly aflatoxin M1. During the previous decade several papers pertaining to aflatoxin M1 have been published in different journals. Not mention of their more or less scientific aspects, they have fundamentally some problems in different features. In this paper we are going to have a bird's eye view on some articles published on this topic. It is suggested that complete research must be performed in order to find out the source of aflatoxin M1 contamination.